Enhancing Multicultural Adaptation among Junior High School Students through Classical Guidance Services: An Action Research Study - tri rizky wulandari; Rafael Lisinus Ginting (Insight: Journal of Counseling and Psychology, 2026)
The increasing cultural diversity within educational settings requires students to develop effective multicultural adaptation skills in order to interact harmoniously with individuals from different backgrounds. However, many adolescents continue to experience difficulties in accepting diversity, building intercultural relationships, and adjusting to multicultural environments. This study aimed to improve students’ multicultural adaptation abilities through classical guidance services. The study employed a Guidance and Counseling Action Research design using a mixed quantitative and qualitative approach implemented in two cycles. The participants consisted of 38 seventh-grade students from SMP Wage Rudolf Supratman 2 during the 2024/2025 academic year. Data were collected through multicultural adaptation questionnaires, structured observations, interviews, and documentation. Quantitative data were analyzed using descriptive statistics, normality testing, and paired-samples t-tests, while qualitative data were analyzed through data reduction, categorization, and interpretation. The findings revealed a consistent improvement in students’ multicultural adaptation abilities across the intervention cycles. The mean score increased from 84.03 (55%) in the pre-cycle stage to 112.10 (74%) in Cycle I and further increased to 136.20 (90%) in Cycle II. Improvements were observed across all dimensions of multicultural adaptation, including adaptation to cultural diversity, building mutual trust, understanding others’ perspectives, and creating harmonious interactions. The results of the paired-samples t-test indicated a statistically significant difference between students’ adaptation levels before and after the intervention (p < .001). Qualitative findings further demonstrated positive behavioral changes, including greater openness, increased respect for diversity, stronger interpersonal trust, and more inclusive social interactions. In conclusion, classical guidance services were found to be effective in enhancing students’ multicultural adaptation abilities. The findings highlight the importance of integrating multicultural values into school guidance programs and provide practical implications for school counselors in promoting inclusive and harmonious educational environments.